Bochdalek hernias in the adult population: a systematic review of the literature. Issue 9 (31st March 2022) - Katsaros, Ioannis; Giannopoulos, Spyridon; Katelani, Stamatia; Vailas, Michail; Sotiropoulou, Maria; Papaconstantinou, Dimitrios; Giannakodimos, Ilias; Kapetanakis, Emmanouil I; Tomos, Periklis; Schizas, Dimitrios
Abstract: Background: Bochdalek hernia (BH) is characterized by the protrusion of viscera into thorax through the posterolateral section of the diaphragm. The aim of this study was to systematically review current literature concerning Bochdalek hernias in adults and elucidate their clinical characteristics and preferable treatment approach. Methods: A search of PubMed and Cochrane bibliographical databases for studies regarding BHs was conducted (last search: 31st March 2021). Results: Predefined inclusion criteria were met by 173 articles and concerned collectively 192 patients (50.5% males) with a mean age of 45.41 ± 20.26 years. Abdominal pain (62.0%) and pulmonary symptoms (41.1%) were the predominant symptomatology of included cases. BHs protruded mainly through the left side of the diaphragm (70.7%), with large intestine (42.7%) and stomach (37.1%) being the most commonly herniated abdominal organs. Most patients (53.8%) underwent an open surgical approach, while abdominal approach was preferred (64.8%). to the thoracic one. Thirty‐day postoperative complication were encountered at 21.5% of patients, while 30‐day mortality reached 4.4%. Conclusion: BH is an extremely rare type of congenital diaphragmatic hernia. It rarely concerns adults, and it manifests with vague gastrointestinal or pulmonary symptoms. Surgical approach is the preferred method for their management with open procedures being preferable at emergency cases, while minimal invasive approach necessitates experienced centers. Further research is needed in order to clarify their true incidence and optimal therapeutic strategy. Abstract : Bochdalek hernia is characterized by the protrusion of viscera into thorax through the posterolateral section of the diaphragm. It is an extremely rare type of congenital diaphragmatic hernia, it rarely concerns adults, and manifests with vague gastrointestinal or pulmonary symptoms. Surgical approach is the preferred method for their management with open procedures being preferable at emergency cases, while minimal invasive approach necessitates experienced centers.